A general study of fundamental solutions in aniotropicthermoelastic media with mass diffusion and voids - Chawla, Vijay; Kamboj, Deepmala (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with the study of a fundamental solution in transversely isotropic thermoelastic media with mass diffusion and voids. For this purpose, a two-dimensional general solution in transversely isotropic thermoelastic media with mass diffusion and voids is derived first.
Keywords: general solution; fundamental solution; thermoelastic; voids; mass diffusion